Zambia Jobs in Value Chains : Opportunities in Agribusiness - Krishnan, Sudha Bala (World Bank, Washington, DC, 2017)
This study analyzes from a jobs perspective two high potential value chains (VCs) in Zambia’s agribusiness sector poultry and aquaculture. With more than 50 percent of workers and over 80 percent of poor Zambians recording themselves in agriculture in the 2010 population census, raising agricultural productivity is a determinant to reduce poverty. Yet small-scale farmers (SSFs) and modern commercial operations in large farms exist in parallel, as SSFs typically use backward production systems with scant capitalization. Zambia’s challenge is to overcome the persistent disconnect between low productivity smallholder agriculture and high productivity modern agribusiness firms. Developing market linkages will enable the agribusiness sector to meet the growing urban demand for food products, while connecting more people to jobs.